INTEGRATION OF LEARNING MANAGEMENT SYSTEMS (LMS) IN TEACHING PHRASEOLOGICAL UNITS (Web of Teachers: Inderscience Research, 2026)
In an increasingly digital educational landscape, the integration of Learning Management Systems (LMS) into foreign language teaching has reshaped how lexical and cultural competencies are developed. This article examines the theoretical foundations, pedagogical rationale, practical applications, and challenges associated with integrating LMS platforms for teaching phraseological units—idioms, collocations, fixed expressions—in foreign language classrooms. Emphasis is placed on existing research in phraseology pedagogy, the functionality of LMS platforms such as Moodle, and instructional design strategies that leverage LMS capabilities. The discussion draws on both linguistic and educational technology scholarship to present a coherent framework for effective integration.